Impact of Dietary Counseling on Nutritional requirements and Mitigating Noncompliance behavior in Hemodialysis Patients: A Pilot Study - Fernandes, Sarita Telma; Dsilva, Fatima (Journal of Health and Allied Sciences NU, 2024)
Introduction Hemodialysis is the most sought-after treatment modality in patients with end-stage renal disease. The success of hemodialysis depends on the patient's adherence to diet and fluid restrictions to a great extent. Nutritional health is a critical consideration, especially for hemodialysis patients. Nutritional education and counseling for renal disease patients significantly preserve renal function and overall well-being.Methods Quantitative research approach with a quasi-experimental crossover design to determine the effectiveness of dietary counseling on the nutritional requirement and noncompliance behavior of patients undergoing hemodialysis conducted at Mangala Kidney Hospital, Mangalore, Karnataka, India.Results The mean age among the participants was 46.07 + 9.67 years. Nearly half of the subjects, 11 (39.29%), had undergone dialysis for 1 to 5 years. Twenty-six (96.3%) had noncompliance behavior toward diet and fluid. Based on biochemical parameters, 20 (74.07%) were classified as low-risk noncompliance and 7 (25.92%) high-risk noncompliance behavior. A paired t-test showed that there is a significant difference in knowledge of nutritional requirements, t (26) = 6.30, p ≤ 0.001 at 5% level of significance, and noncompliance among the participants before and after the dietary counseling program as t (26) = –5.41, p ≤ 0.001 at 5% level of significance.Conclusion Implementing nurse-led counseling for hemodialysis patients can improve biochemical parameters and enhance understanding of dietary and fluid restrictions, positively impacting laboratory indicators.
Keywords: nurse-led dietary counseling; noncompliance behavior; hemodialysis patients; nutritional requirements